Analysis of the Effects of the Economic Crisis in Greece on the Macedonian Economy - Trenovski, Borce (Center for Economic Analyses (CEA), 2010)
The deep economic crisis which currently is "shaking" our neighbour Greece emerged as a new variable in the predictions and planning of the economic activity along with all the main economic variables in the Macedonian economy. In this study we are attempting to determine the potential effects of the Greek economic crises on our economy, having in mind that our neighbour - Greece - is one of the bigger investors and trading partners of our country. The dominant part - the core of the analysis - will focus on determining the effects of the economic crisis in Greece on: foreign effective demand of Macedonia (two scenarios), threatened export sectors and possible options for reducing the effect on those sectors (case study), the effects on the flows of foreign direct investment, the effect of spreading the crisis outside the Greek economy (Euro zone), and other direct and indirect effects connected with the initially mentioned.
Keywords: Greek economic crises, foreign effective demand, export, FDI, Macedonian economy